Adolf Hitler’s Pathological Narcissistic Personality Disorder in Mein Kampf - Fayola Isabelle Hartanto; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Given the argument that an autobiography can be deconstructed like any other fictional texts, this article analyzes Mein Kampf (1939), an autobiography written by Adolf Hitler by treating the text as a fiction. Doing so reveals Adolf Hitler the character, who is very influenced by Adolf Hitler the writer. With the use of Otto F. Kernberg’s (2004) theory on pathological narcissistic personality disorder, this article attempts to find Adolf Hitler the character’s narcissistic personality disorder inside of Mein Kampf and the reasons for such personality disorder. The investigation reveals that the symptoms of the character’s narcissism can be found in the character’s self, emotional life, and social functioning which fit into Kernberg’s (2004) description of a narcissistic patient. On the other hand, the character’s authoritarian parental figure and innate talents are the reasons for the personality disorder. Keywords: autobiography; narcissism; adolf hitler; mein kampf